Wireless Sensor Network deployment inside RA-6 Argentine Nuclear Research Reactor for environmental measurement - Carbajales, Rodrigo José (2015)
In this paper we present a low-cost Wireless Sensor Network (WSN) inside of the Nuclear Research Reactor RA-6 in Argentina. The WSN measures environmental parameters to offer a support system for the operators in the Control Room and to provide readily available information on the internet, for public access or other uses. Wireless sensors, also known as motes, measure radiation, temperature, vibration, light, pressure and send information to a gateway that bridges data between the internet and conventional instrumentation.